Keanekaragaman dan Pola Distribusi Tumbuhan Paku di Taman Hutan Raya Sultan Adam Mandiangin - Gunawan Gunawan; Nurul Huda (Universitas Lambung Mangkurat, 2020)
The research aims to analyze the diversity of ferns, to know the distribution pattern and potential of ferns in TAHURA Mandiangin Sultan Adam. The research included sampling, measurement of environmental parameters as supportive data, identification of ferns samples, and data analysis. The research was conducted from October to December 2011. The research showed that, at different heights there are 548 individuals consisting of 16 species of ferns, including the 8 species of terrestrial and 8 kinds of epiphytic. Ferns are included into two classes, namely, Filicine and Lycopodinae, 6 Order, and 8 families are scattered at heights different. Indices of diversity in zone I-II showed diversity index is medium, in zone III has low species diversity. Distribution pattern is Uniform. The Location of existing research that can be used as ornamental plants, medicinal herbs, and vegetables.